The importance of sleep in learning: from the perspective of neurocience - Aguilar Mendoza, Luis Ángel (2017)
The sleep as a physiological state, is essential for human life and the processes of sleep and learning are essential for the consolidation of memory. This document aims to present a brief review about sleep and its relationship with learning, from the perspective of neuroscience. The first part of the paper provides a description of the stages of sleep and which are the brain structures involved in controlling them. A brief description of the sleep process in neurophysiological activities (immune system, cardiovascular system and endocrine system) is presented. The learning is related to the changes that occur in the individual at the neuronal, cognitive and behavioral level as a result of the exchange of experiences and stimuli, finally seeking the adaptation with their surroundings. Linked to learning is the memory, ability to acquire, retain, store and evoke these exchanges with the outside. According to the information collected, we can state that it is during sleep that it benefits and facilitates neural maintenance, neurogenesis, learning, memory and neuronal plasticity.